Impact of video-based educational intervention on knowledge and perception of polycystic ovarian syndrome among pharmacy students: a pre-post interventional study - Chibueze Anosike; Christabel Ogechukwu Okoye; Nnanyelugo Ogechukwu Isiogugu; Chigozie Gloria Anene-Okeke; Ezinwanne Jane Ugochukwu; Vanessa Chinweike Okonkwo; Japhet Percy Udoh; Maureen Chiamaka Ukpaka; Sonna Ausla Nebonta; Onyinyechi Gift Okpe (BMC Medical Education)
Abstract Background Polycystic ovarian syndrome (PCOS) is the leading cause of anovulatory infertility among women of reproductive age. Pharmacy students and other healthcare trainees have been shown to have limited knowledge of PCOS. Therefore, this study aimed to investigate the impact of video-based educational intervention on knowledge and perception of PCOS among final-year undergraduate pharmacy students in a Nigerian public university. Methods A pre-post video-based interventional study was conducted among all final-year undergraduate pharmacy students in a Nigerian public university. Informed consent was obtained from all eligible participants. Data were collected using a validated self-administered questionnaire before and after administering the intervention. Descriptive statistics, paired t-tests, and independent t-tests were used for data analysis. The level of significance was set as p < 0.05. Results Of the 306 pharmacy students who participated in the study, more than half were female (n = 168, 54.9%), aged 20 to 24 years (n = 166, 54.2%), and had one to three female siblings (n = 189, 61.8%). About 82% of the pharmacy students had heard of PCOS (n = 250). Video-based educational intervention significantly improved pharmacy students’ knowledge of PCOS (90.42 ± 12.85 vs. 47.51 ± 25.97, t = -25.494, p = 0.001). However, there was no significant difference in the students’ perception towards PCOS before and after the intervention (18.35 ± 5.50 vs. 18.33 ± 5.36, t = 0.045, p = 0.965). Conclusion Video-based intervention improved the knowledge of pharmacy students about PCOS, but had no significant impact on their perception towards the disorder. Being a female student was associated with a better understanding and a more positive perception towards PCOS. Clinical trial number Not applicable.